2004
DOI: 10.1002/bmc.292
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of p‐aminosalicylic acid and its degradation product m‐aminophenol in pellets by ion‐pair high‐performance liquid chromatography applying the monolithic Chromolith Speedrod RP‐18e column

Abstract: An ion-pair high performance liquid chromatographic method was developed for the simultaneous determination of p-aminosalicylic acid (PAS) and its degradation product m-aminophenol (MAP) in a newly developed multiparticular drug delivery system. Owing to the concentration differences of PAS and MAP, acetanilide and sulfanilic acid were used as internal standards, respectively. The separation was performed on a Chromolith SpeedROD RP-18e column, a new packing material consisting of monolithic rods of highly por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…HPLC analysis of the active drug PAS in the nanocomposites was carried out by the methods reported by Hong et al (2011) and Vasbinder et al (2004) [36, 37]. In brief, the mobile phase of methanol as solvent A and solvent B phosphate buffer is composed of a 17.5 mM equal amount of monobasic and dibasic potassium phosphate of pH 3.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPLC analysis of the active drug PAS in the nanocomposites was carried out by the methods reported by Hong et al (2011) and Vasbinder et al (2004) [36, 37]. In brief, the mobile phase of methanol as solvent A and solvent B phosphate buffer is composed of a 17.5 mM equal amount of monobasic and dibasic potassium phosphate of pH 3.5.…”
Section: Resultsmentioning
confidence: 99%
“…There were about 1.4 million human deaths from TB and about 8.7 million people infected in 2012 [1, 2]. TB is also the second greatest killer of humans in the world by a single infectious agent after HIV/AIDS [1].…”
Section: Introductionmentioning
confidence: 99%
“…The previously reported method was used with slight modification for PAS quantification 27. The mobile phase used in this work was a combination of methanol and 17.5 mM potassium phosphate buffer (equal molar concentrations of both monobasic and dibasic potassium salts at a pH of 3.5 adjusted by phosphoric acid) at a ratio of 85:15 27. The standard solutions of different PAS concentrations of 0 mg/L, 20 mg/L, 40 mg/L, 60 mg/L, and 80 mg/L were prepared in 50 mL solutions (45 mL mobile phase plus 5 mL HCl).…”
Section: Methodsmentioning
confidence: 99%
“…Studies using unmodified commercial silica monolith columns have already reported considerable improvement in selectivity, efficiency and LOD over conventional columns simply by allowing higher sample throughput while maintaining the favourable mass transfer characteristics, which is not possible with conventional packed particle columns [34]. Several examples of postmodification have been reported, including surfactant-coated RP silica monoliths for ion-exchange [20,21], covalent attachment of functional group substrates [35][36][37], as well as silica monoliths fabricated in a capillary and coated via electrostatic interaction [38].…”
Section: Monolithic Silica Stationary Phasesmentioning
confidence: 99%